SPIRITUAL LEADERSHIP SEBAGAI FUNGSI PENGAWASAN UNTUK MEWUJUDKAN PUSTAKAWAN YANG UNGGUL - Jamzanah Wahyu Widayati (Jurnal Pustaka Ilmiah, 2016)
Librarians have a competency that can not be underestimated, both soft skills and hardskills. Competences of the librarians should make himself as a person who is expertin carrying out the tasks entrusted to him. This paper describes how the spiritualleadership delivers librarians become superior person by instilling a work ethic andIslamic Prophet modelling in the library working dynamics. Spiritual leadership hereact as a supervisory function to form a self awareness that librarians are leader forhimself with direct supervisory control of God.